Textbook of Histology and a Practical Guide - Gunasegaran, Jp. (India : Elsevier, 2010)
This book is designed for undergraduate medical and dental students. The present updated edition is an illustrated account of microscopic structures of tissues and organs in a simple and precise language. The text is extremely student-friendly. Concise, point-wise presentation of text for easy learning and quick recapitulation during exams Line diagrams for basic understanding of the tissues/organs Pencil sketches of sections (haematoxylin & eosin stained) along with salient points of identification, well integrated with text for understanding technical details of.
Keywords: Histology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; MEDICAL -- Anatomy